Effective Digital Marketing Strategy to increase Online Sales - Jusuf, Dewi Indriani (Jurnal Pendidikan Indonesia, 2022)
With the increasing popularity of online shopping, it is important for companies to adopt the right digital marketing strategies to maintain and increase their market share. This research aims to analyze and identify effective digital marketing strategies to increase sales in the online business environment. This research uses a qualitative approach with descriptive methods. The research results show that implementing a combination of effective digital marketing strategies, including SEO, content marketing, social media marketing, persuasive copywriting, personalized email marketing, and paid advertising, can significantly increase brand awareness, consumer engagement, and ultimately increase conversion rates. and online sales. By deeply understanding consumer preferences and behavior, companies can optimize their marketing strategies to achieve more effective and measurable results, and strengthen their position in an increasingly competitive and digitally dynamic market.